A Diversity Ideology Intervention: Multiculturalism Reduces the Racial Achievement Gap. Issue 5 (July 2021) - Birnbaum, Hannah J.; Stephens, Nicole M.; Townsend, Sarah S. M.; Hamedani, MarYam G.
In the United States, underrepresented racial minority (URM) students continue to face psychological barriers that undermine their achievement and fuel disparities in academic outcomes. In the current research, we tested whether a multicultural ideology intervention could improve URM students' grade point averages (GPAs) during the first 2 years of college and thereby reduce the racial achievement gap. Specifically, first-year college students ( N = 407) read a diversity statement that represented the schools' diversity ideology in terms of either multiculturalism or colorblindness. URM students who read a multicultural diversity statement earned higher GPAs 2 years later compared to those who read a colorblind diversity statement. Furthermore, they earned higher GPAs compared to a nonparticipant campus-wide control group. The current study is the first to demonstrate that multiculturalism can increase the long-term academic outcomes of URM students in college.